Clinical and epidemiological characteristics and hormonal profile of adult females with acne vulgaris: a cross-sectional study from a tertiary care hospital - Shah, Nidhi; Ali, Faaria; Radhakrishnan, Aswathy; Chaudhari, Parag; Patil, Anant; Patil, Sharmila (International Journal of Research in Dermatology, 2021)
Background: To study clinical and epidemiological characteristics and hormonal profile of adult females with acne Methods: Adult female patients of >25 years of age with acne were enrolled. Demographic profile, habits, location of acne lesions, associated disease and acne flare association with menstrual cycle were noted. Prevalence of abnormalities in testosterone, dihydroepiandrosterone-sulfate (DHEAS), prolactin, luteinizing hormone (LH), follicle stimulating hormone (FSH), LH:FSH ratio, anti-mullerian hormone (AMH), and serum insulin were noted. Ultrasound (abdomen and pelvis) was performed for screening the presence of any abnormality. Results: Fifty one patients [mean (SD) age 30.96 (4.93) years] were included in the study. Thirty six (70.59%) patients had persistent type of acne. Grade 2 acne was present in 40 (78.43%) patients. Oily skin was seen in 27 (52.94%) patients. Hirsuitism and menstrual irregularity was present in 24 (47.06%) and 13 (25.49%) patients respectively. Pigmentation and scarring was present in 27 (52.94%) and 35 (68.63%) patients respectively. Acne lesions were seen on cheeks in 36 (70.59%) patients. Eight (15.69%) patients had elevated testosterone. DHEAS and prolactin levels were normal in all patients. Elevation of LH and decreased FSH levels were seen in five (9.80%) and three (5.88%) patients respectively. Five (9.80%) patients had elevated LH:FSH level. Raised insulin level was seen in 8 (15.69%) patients. Conclusions: Derangement of hormonal profile is not very common among adult female patients with acne. However, in some patients laboratory markers of hyperandrogenism are seen.